Evaluating the Employment Effects of Job Creation Schemes in Germany - Thomsen, Stephan Lothar (ZEW Economic Studies, 2007)
This book analyses the employment effects of job creation schemes for the participating individuals in Germany. Programmes provide subsidised jobs that are additional in nature and of value for society to hard-to-place individuals. International evidence on the effectiveness suggests that programmes should be targeted to the needs of the unemployed and should be offered early in the unemployment spell. Both questions are studied for job creation schemes in Germany. In the empirical analysis, propensity score matching methods extended to the dynamic setting are applied to administrative data of the Federal Employment Agency.